Tackling the backlash: Dealing with internal and external criticism of D&I initiatives - Daniel Wolfgruber; Sabine Einwiller; Michelle Wloka (Academic Society for Management & Communication, 2022)
Even though genuine D&I management, which aims at fostering an inclusive work environment, can lead to economic benefits while promoting a fairer world, it is frequently subject to criticism. A research project consisted of two empirical studies led by Professor Sabine Einwiller and Daniel Wolfgruber at University of Vienna investigated why negative reactions towards D&I initiatives emerge, and what companies can do about them. You can find further information in the new edition of the Communication Insights. – – Themen rund um Diversität und Inklusion (D&I) erhalten seit geraumer Zeit verstärkte öffentliche Aufmerksamkeit - positive wie negative. Prof. Dr. Sabine Einwiller und Daniel Wolfgruber (Universität Wien) stellen die zentralen Forschungsergebnisse ihrer neusten Studie zu internem und externem Widerstand zu D&I-Kommunikation vor und diskutieren Lösungsansätze im Umgang mit Kritik. Nähere Informationen zu den Forschungsergebnissen können in der neuesten Ausgabe der Communication Insights nachgelesen werden.
Keywords: 650